Variability in the lymph node retrieval after resection of colon cancer: Influence of operative period and process. Issue 31 (August 2016) - Choi, Jung Pil; Park, In Ja; Lee, Byung Cheol; Hong, Seung Mo; Lee, Jong Lyul; Yoon, Yong Sik; Kim, Chan Wook; Lim, Seok-Byung; Lee, Jung Bok; Yu, Chang Sik; Kim, Jin Cheon
Abstract : Abstract: The purpose of this study was to evaluate variations in the number of retrieved lymph nodes (LNs) over time and to determine the factors that influence the retrieval of <12 LNs during colon cancer resection. Patients with colon cancer who were surgically treated between 1997 and 2013 were identified from our institutional tumor registry. Patient, tumor, and pathologic variables were evaluated. Factors that influenced the retrieval of <12 LNs were evaluated using multivariate logistic regression modeling, including time effects. In total, 6967 patients were identified. The median patient age was 61 years (interquartile range [IQR] = 45–79 years) and 58.4% of these patients were male. The median number of LNs retrieved was 21 (IQR = 14–29), which increased from 14 (IQR = 11–27) in 1997 to 26 (IQR = 19–34) in 2013. The proportion of patients with ≥12 retrieved LNs increased from 72% in 1997 to 98.8% in 2013 ( P  < 0.00001). This corresponded to the more recent emphasis on a multidisciplinary approach to adequate LN evaluation. The number of retrieved LNs was also found to be associated with age, sex, tumor location, T stage, and operative year. Tumor location and T stage influenced the number of retrieved LNs, irrespective of the operative year ( P  < 0.05). Factors including a tumor location in the sigmoid/left colon, old age, open resection, earlier operative year, and early T stage were more likely to be associated with <12 recovered LNs ( P  < 0.5; chi-squared test) ( P  < 0.001). The total number of retrieved LNs may be influenced by tumor location and T stage of a colon cancer, irrespective of the year of surgery. LN retrieval after colon cancer resection has increased in recent years due to a better awareness of its importance and the use of multidisciplinary approaches.